2021
DOI: 10.6007/ijarbss/v11-i5/9934
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity among University Students

Abstract: Physical activity is essential for health protection and disease prevention. However, university students are more willing to spend more time studying than participating. Research has shown in recent years that barriers lead to the lack of young adults' involvement in physical activity. This paper mainly aims to investigate differences in attributes towards the engagement of students in physical activity. A cross-sectional survey of undergraduate students was carried out at selected faculties. A self-administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A systematic review of 21 studies in total reported that the level of physical activity among university students was moderate [ 30 ]. Another study found that half of the university students participating in the study were less active/inactive [ 31 ]. On the other hand, the data obtained from these studies indicate that especially males are more active or, similar to our study, although the level of physical activity is higher in males, it is not statistically significant [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 21 studies in total reported that the level of physical activity among university students was moderate [ 30 ]. Another study found that half of the university students participating in the study were less active/inactive [ 31 ]. On the other hand, the data obtained from these studies indicate that especially males are more active or, similar to our study, although the level of physical activity is higher in males, it is not statistically significant [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The college period is a transition to adulthood which is a critical moment that can determine a person's lifestyle (Carney et al, 2000;Naudeau et al, 2008). Although an active lifestyle has an essential role in maintaining fitness, physical and mental health, as well as academic achievement, almost half of the student population is classified as lacking physical activity (PA) (Keating et al, 2005;Anuar et al, 2021). In addition, the novel coronavirus disease 2019 (COVID-19) pandemic exacerbated the physical inactivity among university students.…”
Section: Introductionmentioning
confidence: 99%